2017
DOI: 10.1037/cdp0000146
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic/racial discrimination moderates the effect of sleep quality on school engagement across high school.

Abstract: Objective Previous research has indicated that school engagement tends to decline across high school. At the same time, sleep problems and exposure to social stressors such as ethnic/racial discrimination increase. The current study uses a biopsychosocial perspective to examine the interactive and prospective effects of sleep and discrimination on trajectories of academic performance. Method Growth curve models were used to explore changes in 6 waves of academic outcomes in a sample of 310 ethnically and rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 102 publications
1
18
0
Order By: Relevance
“…School engagement was another outcome of exposure to movement behaviors that was a unique consideration in our study. In prior research, sleep and physical activity have been shown to individually predict school engagement in adolescents with ADHD [ 10 , 32 ]. As an extension of previous findings, a dose-response association between the number of movement guidelines met and school engagement was observed in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…School engagement was another outcome of exposure to movement behaviors that was a unique consideration in our study. In prior research, sleep and physical activity have been shown to individually predict school engagement in adolescents with ADHD [ 10 , 32 ]. As an extension of previous findings, a dose-response association between the number of movement guidelines met and school engagement was observed in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies examined the association between sleep duration and academic achievement in children and youth. Two studies used a longitudinal design; one study reported that short sleep duration did not predict cumulative grade point averages at follow-up [111]. The other study reported nonlinear positive associations of sleep duration with grade point average and English test scores [103].…”
Section: Sleepmentioning
confidence: 99%
“…Recently Dunbar, Mirpuri, and Yip, [16] carried out a study in the US using the bio-psychosocial model in which they explored schoolengagement among a group of ethnically diverse adolescents with a mean age of 14.47 years. They assessed academic outcome, sleep quality, duration and grades.…”
Section: Discussionmentioning
confidence: 99%
“…That study suggested that factors such as stress could have an impact on an individual's ability to manage conflicts and that any continual-stress could have implications from a physiologicalperspective. The study could be seen as one example of how the bio-psychosocial model can be applied to understand the complex-interaction of a range of factors which could impact the health of an adolescent, particularly with regards to sleep-quality [16].…”
Section: Discussionmentioning
confidence: 99%